2007
DOI: 10.1111/j.1525-1594.2007.00483.x
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related Quality of Life in Patients on Peritoneal Dialysis in Serbia: Comparison with Hemodialysis

Abstract: Patients' health-related quality of life (HRQoL) is an important indicator of the effectiveness of the medical care they receive. Patients who reach end-stage renal disease are older and have a considerable extent of comorbidity. The objectives of this study were (i) to evaluate HRQoL in patients at the initiation of continuous ambulatory peritoneal dialysis (CAPD) treatment (incident cohort) and in patients on long-term CAPD therapy (prevalent cohort), and (ii) to compare influence of comorbidity on HRQoL in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 30 publications
1
11
1
Order By: Relevance
“…HRQoL can be evaluated at a slightly poor level in PD patients compared with the previous studies. 2,13,19,20,22 Although our scores are in accordance with some studies, [23][24][25][26][27][28][29] they are negated by others. 1,19,30 Previous studies using the SF-36 scale in Turkey have shown that the PCS and MCS scores were higher than ours.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…HRQoL can be evaluated at a slightly poor level in PD patients compared with the previous studies. 2,13,19,20,22 Although our scores are in accordance with some studies, [23][24][25][26][27][28][29] they are negated by others. 1,19,30 Previous studies using the SF-36 scale in Turkey have shown that the PCS and MCS scores were higher than ours.…”
Section: Discussionsupporting
confidence: 89%
“…4,13,19,[22][23][24]29,[31][32][33] MCS and PCS scores in our study were similar to those in studies reported from Serbia, France, and Mexico. 2,28,30 However, MCS in our study was slightly lower than that of the United Kingdom, the United States, and the Netherlands, whereas PCS was higher than that of the United Kingdom and the United States. 13,23,24,34 Finally, the mean summary scores of HRQoL in PD patients in Turkey are almost at the same level as in developed countries.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…CAPD pa ti ents had sig ni fi cantly hig her pa rame ters of HRQOL than HD pa ti ents. 24 Ci nar et al sta ted that PD po pu la rity was in cre a sed in the last ye ars be ca u se its is a simp le, com for tab le, and inex pen si ve tre at ment met hod. 5 Similarly Er soy et al sta ted that PD was su i tab le for yo ung, physically ac ti ve pa ti ents who do not want to be de pendent on mac hi nes.…”
Section: Discussionmentioning
confidence: 99%
“…19 In so me ot her stu di es QOL sco res we re higher in the CAPD pa ti ents. [20][21][22][23][24] The study of Ka lender et al whe re SF-36 was used to eva lu a te QOL of chro nic kid ney di se a se pa ti ents re por ted that the SF-36 sco res we re hig her in the CAPD gro up than HD gro up. 20 Shrest ha et al sta ted that pa ti ents on CAPD ha d bet ter qu a lity of li fe than pa ti ents on HD es pe ci ally in terms of men tal he alth.…”
Section: Discussionmentioning
confidence: 99%